Pengaruh Literasi Digital dan Literasi Kewarganegaraan terhadap Tingkat Ketahanan Pribadi Siswa Sekolah Menengah Kejuruan - Saidi, Mohammad Ridwan; Supriyono, Supriyono; Al-Atok, A. Rosyid (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the level of digital literacy, civic literacy, and personal resilience of vocational high school students in Malang City and analyze the influence of digital literacy and civic literacy on student personal resilience linearly and simultaneously. This study used a quantitative approach with a survey method. Using the cluster proportional random sampling technique, a sample of 313 students spread proportionally from SMKN throughout Malang City was obtained. Data was collected using interview techniques, questionnaires or questionnaires, and documentation. Data analysis used descriptive data analysis and inferential data analysis. The study results showed that the overall digital literacy of students was in a decent category. The overall civic literacy of students was included in the excellent category. Students' overall personal resilience was included in the excellent category. Digital literacy positively affected students' resilience with a significance value of 0.024. Civic literacy positively affected students' resilience with a significance value of 0.041. Digital literacy and civic literacy simultaneously affected students' resilience with a significance of 0.02.